Traffic Learning Model Development Through RSPA Program (Road Safety Partnership Action) Community Based - Supriatna, Dede Ahmad (Universitas Pendidikan Indonesia (UPI), 2022)
Traffic is the lifeblood of life because everyone from birth to death needs and uses traffic facilities, for this reason security, safety, comfort and smooth traffic must be guaranteed so that transportation can be enjoyed by all users comfortably and avoid from unwanted things. How to make it happen so that people feel comfortable in passing through this traffic, of course there must be a concept that can answer it, RSPA (Road Safety Partnership Action) is the flagship program of the Korlantas Polri to be able to work together with the community of road users who partner with the Police, especially those who are members of the community can work together together create security, safety, reliability and smooth traffic, through continuous and sustainable traffic learning for all its members so that they can become pioneers of the traffic order and can invite, deliver, campaign directly to the public, and can reduce the number of accidents the traffic going on. The research method that will be used is descriptive qualitative, explaining a phenomenon and constructing a theory related to the phenomenon as well as providing a systematic and accurate description of the actual facts and characteristics of a particular community